Prevalence and management of iron overload in pyruvate kinase deficiency: report from the Pyruvate kinase deficiency natural history study - Beers, E.J. (Ward) van; Kunz, Joachim (Haematologica, 2019)
Pyruvate kinase (PK) deficiency is the most common red cell glycolytic enzyme defect causing hereditary non-spherocytic hemolytic anemia. Current treatments are mainly supportive and include red cell transfusions and splenectomy.[1][1] Regular red cell transfusions are known to result in iron